Characterization and Prognosis Significance of JAK2 (V617F), MPL, and CALR Mutations in Philadelphia-Negative Myeloproliferative Neoplasms - Singdong, Roongrudee (Asian Pac J Cancer Prev, 2016)
BACKGROUND: The discovery of somatic acquired mutations of JAK2 (V617F) in Philadelphia-negative myeloproliferative neoplasms (Ph-negative MPNs) including polycythemia vera (PV), essential thrombocythemia (ET), and primary myelofibrosis (PMF) has not only improved rational disease classification and prognostication but also brings new understanding insight into the pathogenesis of diseases. Dosage effects of the JAK2 (V617F) allelic burden in Ph-negative MPNs may partially influence clinical presentation, disease progression, and treatment outcome. MATERIAL AND METHODS: Pyrosequencing was performed to detect JAK2 (V617F) and MPL (W515K/L) and capillary electrophoresis to identify CALR exon 9 mutations in 100 samples of Ph-negative MPNs (38.0 PV, 55 ET, 4 PMF, and 3 MPN-U). RESULTS: The results showed somatic mutations of JAK2 (V617F) in 94.7% of PV, 74.5% of ET, 25.0% of PMF, and all MPN-U. A high proportion of JAK2 (V617F) mutant allele burden (mutational load > 50.0%) was predominantly observed in PV when compared with ET. Although a high level of JAK2 (V617F) allele burden was strongly associated with high WBC counts in both PV and ET, several hematological parameters (hemoglobin, hematocrit, and platelet count) were independent of JAK2 (V617F) mutational load. MPL (W515K/L) mutations could not be detected whereas CALR exon 9 mutations were identified in 35.7% of patients with JAK2 negative ET and 33.3% with JAK2 negative PMF. CONCLUSIONS: The JAK2 (V617F) allele burden may be involved in progression of MPNs. Furthermore, a high level of JAK2 (V617F) mutant allele appears strongly associated with leukocytosis in both PV and ET.